Analisis Strategi Pusat Pendidikan dan Pelatihan Perdagangan Menuju Corporate University - Nadya Megawati Rachman (Pusat Pendidikan dan Pelatihan Perdagangan, 2019)
In order to increase the capacity and quality of human resources at the Ministry of Trade, the Center for Trade and Education has an important role in supporting the achievement of the vision and mission and the application of organizational cultural values of the Ministry of Trade. Innovations in the learning process must be implemented in the face of the demands of globalization and the times. The purpose of this study is to analyze the Strategic Center of Trade Training and Education towards Corporate University. The analytical method used in this study is to use IFE-EFE matrix analysis, IE matrix, SWOT analysis and Qualitative Strategic Planning (QSP) matrix. Based on the results of the analysis conducted by the Trade Training Center, it is expected to implement the S-O strategy, namely strengthening the implementation of learning organizations with the Visionary Leadership approach as the main priority strategy generated from the QSP matrix analysis. Keywords : Corporate University, IFE-EFE matrix, IE matrix, SWOT, QSPM